PENGARUH KONDISI EMOSI TERHADAP PEMBELIAN KOSMETIK SECARA DARING - Pratita Rara Raina (Akademi Seni dan Desain Indonesia Surakarta, 2023)
Impulsive buying behavior has been known since years ago, in fact the research about impulsive buying behavior has been done since early 70s. Impulsive buying behavior has been known with the sudden urge to buy something without intention or plan at earlier time. This research refers to earlier research about “Impulsive Buying Trait: An Effective Moderator for Shopping Emotions and Perceived Risk.” However this research omitted several variables such as perceived risk, impulsive buying intention, and impulsive buying trait, since three of them was not relevant Vol. 9 | No. 1 | Tahun 202324to the research. Generally, this research was to know the effect of emotional states to impulsive buying behavior.The object of this research was online cosmetic purchase, which was specifically targeted women who have been shopping cosmetics online for at least 5 times and for the last 6 months (from July – December 2015) she at least shop for 3 times. The data gathered by online questionnaire and the respondents were tested their validity by answering several questions about their online cosmetics purchase frequency. Respondents consist of 272 people who mostly are university students. Data then analyzed using logistic regression to test the hypothesis.The result showed that emotional states positively associated with impulsive buying behavior.Keyword: Arousal, Dominance, Emotional States, Impulsive Buying Behavior, Impulsive Buying Trait, Pleasure